Analisis Kepercayaan Donatur Melalui Akuntabilitas dan Transparansi Dana Donasi Online Perspektif Akuntansi Syariah - Ahmad Resky; Nurmala Nurmala; Naysilla Difya Febrianti; Aulia Ramadani; Masyhuri Masyhuri (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
The development of digital technology has transformed philanthropic practices through online donation platforms that facilitate the collection and distribution of social funds. However, this development has also created challenges, particularly the low level of public trust in donation fund management due to a lack of transparency and accountability. This study aims to analyze donor trust through the aspects of accountability and transparency in online donation funds from the perspective of Islamic accounting. The study employs a literature review method with a qualitative descriptive approach by examining various relevant books and scientific journals. The findings indicate that accountability and transparency play significant roles in building and maintaining donor trust. Accountability is reflected in clear responsibility for fund management, while transparency is demonstrated through open access to information regarding the collection, utilization, and distribution of donation funds. From the perspective of Islamic accounting, these principles are aligned with the values of amanah (trustworthiness), justice, and openness, which serve as the foundation for managing social funds in Islam. Therefore, the implementation of accountability and transparency supported by Islamic accounting principles can enhance donor trust and promote the sustainability of professional and trustworthy online donation management